Evidence to Support the Clinical Utility of Prenatal Exome Sequencing in Evaluation of the Fetus with Congenital Anomalies: Scientific Impact Paper No. 64 [February] 2021. (15th February 2021) - Mone, F; McMullan, DJ; Williams, D; Chitty, LS; Maher, ER; Kilby, MD; ,; ,
Plain language summary: Structural differences (congenital anomalies) in the makeup of the baby's heart, brain and other organs are found on antenatal ultrasound scans in up to 3% of pregnancies. These often have a genetic cause, arising because of changes in the chromosomes (which store our genetic material) or the DNA code that make up the genes. The more differences a baby has the more likely the risk of underlying genetic disease. If a structural difference is found, parents are usually offered a genetic test, which may be carried out on cells taken either from the placenta (chorionic villous sampling) or the fluid surrounding the baby (amniocentesis). At the moment, these cells are only tested for changes in the chromosomes and are only able to reveal the underlying cause in about 40% of unborn babies. Prenatal exome sequencing (ES) is a new genetic test, which, when combined with testing the DNA of both parents can find changes in the baby's genetic code. If a DNA change is found that can explain the structural changes seen on ultrasound, specific information about the underlying diagnosis can be given to the parents. Having this information can help parents make important decisions about their ongoing pregnancy, as well as help doctors to care for the mother and baby. Finding a genetic change can also help to understand how the condition has arisen and whether it might happen again in another pregnancy. It may also be possible to test for the genetic condition in future pregnancies. Although prenatal ES is an exciting new way to improve diagnosis rates for structural differences, it has some challenges. While the test is very detailed, it may not always find a genetic explanation and sometimes the results are difficult to interpret. For example, genetic changes can be found where their significance for the pregnancy is unclear. More recently, two studies have now shown that prenatal ES can find a genetic diagnosis in at least 10% of pregnancies with structural differences where standard chromosome testing has been negative. This paper reviews these studies, along with earlier evidence on ES and provides clinicians with guidance for future practice.